Detection of Hematopoietic Stem Cell Transcriptome in Human Fetal Kidneys and Kidney Organoids Derived From Human Induced Pluripotent Stem Cells - Hwang, Jin Wook; Desterke, Christophe; Loisel-Duwattez, Julien; Griscelli, Frank; Bennaceur-Griscelli, Annelise; Turhan, Ali G. (Frontiers in Cell and Developmental Biology, 2021)
Background: In mammalians, hematopoietic stem cells (HSC) arise in the dorsal aorta from the hemogenic endothelium, followed by their migration to fetal liver and to bone marrow. In zebrafish, kidney is the site of primary hematopoiesis. In humans, the presence of HSC in the fetal or adult kidney has not been established. Methods: We analyzed the presence of HSC markers in human fetal kidneys by analysis of single-cell datasets. We then analyzed in kidney organoids derived from iPSC, the presence of hematopoietic markers using transcriptome analyses. Results: 12 clusters were identified of stromal, endothelial, and nephron cell type-specific markers in the two fetal stage (17 weeks) kidney datasets. Among these, expression of hematopoietic cells in Cluster 9 showed expression of primitive markers. Moreover, whole transcriptome analysis of our iPSC-derived kidney organoids revealed induction of the primitive hematopoietic transcription factor RUNX1 as found in the human fetal kidney cortex. Conclusions: These finding support the presence of cells expressing HSC transcriptome in human kidney. The mechanisms of the appearance of the cells with the same transcriptional features during iPSC-derived kidney organoid generation requires further investigation.